2022
DOI: 10.1017/s1368980022002191
|View full text |Cite
|
Sign up to set email alerts
|

Digital marketing of online food delivery services in a social media platform before and during COVID-19 pandemic in Brazil

Abstract: Objective: To describe the promotion of food and beverage and marketing strategies used by online food delivery services (OFDS) in a social media platform before and during the pandemic in Brazil. Design: Publicly available data were extracted from OFDS Instagram accounts. Posts published six months immediately before and after the first case of COVID-19 in Brazil were randomly sampled. Two independent authors coded the posts’ content. Food and beverage items featured in posts were class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…Given this scenario, the digital food environment is related to an obesogenic environment, as it shows characteristics similar to a 'food swamp', in which there is a high presence of foods considered markers of unhealthy eating [5]. The characteristics of food marketed via food delivery apps are similar to food often consumed at outside home establishments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given this scenario, the digital food environment is related to an obesogenic environment, as it shows characteristics similar to a 'food swamp', in which there is a high presence of foods considered markers of unhealthy eating [5]. The characteristics of food marketed via food delivery apps are similar to food often consumed at outside home establishments.…”
Section: Discussionmentioning
confidence: 99%
“…However, the habit of purchasing food via online applications did not decrease after the end of the social isolation measures caused by the COVID-19 pandemic. Studies have shown that this behavior was established even with the return to activities and established itself as a new way of accessing food [5,12,13]. Considering the isolation period, our findings corroborate those of the CONVID Behavior Research study, carried out between 24 April and 24 May 2020, with a sample of 45,161 adult individuals living in Brazil, which showed a reduction in the frequency of the consumption of foods considered markers of healthy eating and, in parallel, an increase in the consumption of foods that are markers of unhealthy eating [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The user can also access a list of the most popular or nearest establishments and choose their meal by the terms that characterise each establishment. Marketing strategies, such as illustrative photos and advertisements of meals with discounts or without delivery charges, are frequent in MDA (6)(7)(8)(9)(10)(11) and improve the user experience on the platform and influence the user's decision to purchase (2) . Due to the characteristics of convenience and practicality, the use of MDA has grown.…”
mentioning
confidence: 99%